PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, FASILITAS KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT MUTIFA MEDAN - Ritonga, Sinar; Munthe, Kornel; Situmorang, Aston L. (UNIKA Santo Thomas, 2024)
ABSTRACT The aim of this research is to analyze the influence of human resource development, work facilities and incentives on employee performance at PT Mutifa Medan. Data was obtained from respondents with a population of 40 employees and using a saturated sampling technique, the sample size was also 40 employees. The analysis technique used in this research is multiple linear regression with the validity, reliability and classical assumptions first tested and then the F test and t test carried out. The research results show that HR development, facilities and incentives simultaneously have a significant effect on employee performance, HR development, work facilities and incentives partially have a positive and significant effect on employee performance at PT. Mutifa Medan, and the R2 coefficient value is 0.840, this shows that variations in employee performance can be explained by variations in HR development, facilities and incentives of 84% while another 16% can be explained by other factors.